Spinal cord injury impairs cardiovascular capacity in elite wheelchair rugby athletes - Gee, C. M.; Currie, K. D.; Phillips, A. A.; Squair, J. W.; Krassioukov, A. V. (Clinical Journal of Sport Medicine, 2020)
To examine differences in heart rate (HR) responses during international wheelchair rugby competition between athletes with and without a cervical spinal cord injury (SCI) and across standardized sport classifications. Design: Observational study. Setting: The 2015 Parapan American Games wheelchair rugby competition. Participants: Forty-three male athletes (31 ± 8 years) with a cervical SCI (n = 32) or tetraequivalent impairment (non-SCI, n = 11). Main Outcome Measures: Average and peak HR (HRavg and HRpeak, respectively). To characterize HR responses in accordance with an athletes' International Wheelchair Rugby Federation (IWRF) classification, we separated athletes into 3 groups: group I (IWRF classification 0.5-1.5, n = 15); group II (IWRF classification 2.0, n = 15); and group III (IWRF classification 2.5-3.5, n = 13). Results: Athletes with SCI had lower HRavg (111 ± 14 bpm vs 155 ± 13 bpm) and HRpeak (133 ± 12 bpm vs 178 ± 13 bpm) compared with non-SCI (both P < 0.001). Average HR was higher in group III than in I (136 ± 25 bpm vs 115 ± 20 bpm, P = 0.045); however, SCI athletes showed no difference in HRavg or HRpeak between groups. Within group III, SCI athletes had lower HRavg (115 ± 6 bpm vs 160 ± 8 bpm) and HRpeak (135 ± 11 bpm vs 183 ± 11 bpm) than non-SCI athletes (both P < 0.001). Conclusions: This study is the first to demonstrate attenuated HR responses during competition in SCI compared with non-SCI athletes, likely due to injury to spinal autonomic pathways. Among athletes with SCI, IWRF classification was not related to differences in HR. Specific assessment of autonomic function after SCI may be able to predict HR during competition and consideration of autonomic impairments may improve the classification process.